Penerapan Pola Zero Waste pada Ready to Wear dengan Texstil Ecoprint Pewarna alam - Arina Haq; Grace Nauli (Garina, 2025)
The implementation of the concept of sustainable fashion is an effort carried out by fashion players to create sustainable fashion products so as to reduce the impact of fast fashion. Forms of implementing the concept of sustainable fashion include the zero waste puttern cutting technique and the use of natural dyes. Cutting techniques without leaving scraps and liquid waste produced from the textile production process. The purpose of the study was to determine the process of implementing zero waste in ready to wear with ecoprint natural dye textiles. The data collection methods used are observation, documentation and literature methods. The analysis used in this study is qualitative data analysis. The process begins with creating ecoprint motifs using steam techniques and adding cibori motifs, the process of creating designs and planning the layout of the pattern components, and planning the layout of patterns on ecoprint materials, the cutting process, installing tricot, followed by the sewing process to unite the pattern components. The initial stage in this process is sewing the top. Conclusion of the process of applying the zero waste puttern cutting technique with ecoprin natural dye textiles is one of the visionary concepts where creating clothes starts from making motifs. with ecoprin natural dye textile is one of the visionary concepts where creating clothes starts from making motifs with natural dyes and continues with efforts to minimize fabric waste by applying the zero waste concept to the cutting pattern process and continues with the sewing process until completion, so that it can be used as a solution and reference in the fashion field for making clothes sustainably. Suggestions for applying the zero waste concept to be more optimal, the design of motif designs and pattern designs should always go hand in hand so that all motifs can be used and in accordance with the design to minimize fabric waste and dye waste.